Cover Picture: Immobilization of Recombinant Endo‐1, 4‐β‐xylanase on Ordered Mesoporous Matrices for Xylooligosaccharides Production 38/2019). Issue 38 (18th October 2019) - Shivudu, Godhulayyagari; Khan, Sourav; Chandraraj, Krishnan; Selvam, Parasuraman
Abstract : The cover picture shows the steps for the production of Xylooligosaccharides (XOS). They are emerging prebiotics and their widespread application as food supplements as well as their usage in cosmetic, pharmaceutical and agricultural industry make them attractive. Xylooligosaccharides are formed by the hydrolysis of Xylan with endoxylanase enzyme. In this study, the recombinant endo‐1, 4‐β‐xylanase (XynC) of B. subtilis KCX006 was immobilized onto mesoporous matrices of silica (SBA‐15), carbon (CMK‐3), and zirconia (ZMF‐128). The resulting heterogeneous catalysts produce short‐chain Xylooligosaccharides (X2‐X6) from beech‐wood Xylan and extracted crude Xylans from both sugarcane bagasse and sorghum biomass. In particular, the enzyme immobilized silica (XynC/SBA‐15) produces higher X2‐X6 Xylooligosaccharides and retains larger initial activity (85‐93 %) even after four repeated uses. More information can be found in the Full Paper by Chandraraj and Selvam et al. (DOI:10.1002/slct.201901593 )